CFD modeling of airflow distribution in high-rise warehouse - Terziev Angel; Zlateva Penka; Ivanov Martin; Dimchev Ivan; Vassilev Momchil (E3S Web of Conferences)
The presented study focuses on type “A+” high-rise warehouses, which are 38 meters high and are equipped with specialized indoor climate control systems, providing strictly defined narrow temperature limits all year round. The analyzed air conditioning system includes roof air conditioners operating in fresh air or partial and full recirculation mode. By using the Computational fluid mechanics (CFD) based simulations of the air distribution, it is established that the standard and normative methods for designing such types of systems are not precise enough, to achieve the required parameters of the indoor environment. Analysis of the results shows that stagnation zones often occur in high-rise warehouses, which cannot be eliminated only by “mechanical” rearrangement of air conditioning devices. Overcoming these problems requires the integration of additional impulse mixing devices, to provide better air distribution and improve mixing efficiency throughout the volume. Thus, it can be guaranteed that the parameters of the indoor environment are maintained within the specified range all year round.